Modular construction of macrocycle-based topological polymers via high-efficient thiol chemistry. Issue 15 (2nd March 2015) - Zhao, Junfei; Zhou, Yanyan; Li, Yiwen; Pan, Xiangqiang; Zhang, Wei; Zhou, Nianchen; Zhang, Ke; Zhang, Zhengbiao; Zhu, Xiulin
Abstract : Tadpole-, spiro-shaped, fused-dicyclic tadpole and other complex macrocycle-based topological polymers were modularly constructed via thiol-X chemistry. Abstract : Modular and precise construction of topological polymers with structural complexity is a prerequisite to understand the structure-property relationships of functional non-linear macromolecules. In this article, several examples of well-defined topological polymers are prepared by using two kinds of functionalized cyclic polymeric precursors via different high-efficient thiol-related chemistries. Firstly, multifunctional atom transfer radical polymerization (ATRP) initiators bearing alkyne and disulfide groups were elaborately prepared. Well-defined thiol-containing monocyclic and fused-bicyclic polymers via ATRP and Cu-catalyzed azide–alkyne cycloaddition (CuAAC) ring closure were then synthesized. Finally, by the utilization of thiol-containing monocyclic or fused-dicyclic polymers as building blocks, several kinds of macromolecules with tadpole-, spiro-shaped, fused-dicyclic tadpole and other topologies were successfully constructed via a modular mode. This study expands the scope of available macrocycle-based topological polymers and facilitates further diverse development of even more complex non-linear macromolecules via modular synthetic methodology.